2006
DOI: 10.1104/pp.106.090449
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Tobacco Plants Overexpressing Chloroplastic Ferredoxin-NADP(H) Reductase Display Normal Rates of Photosynthesis and Increased Tolerance to Oxidative Stress

Abstract: (M.P., H.T., M.-R.H.)Ferredoxin-NADP(H) reductase (FNR) catalyzes the last step of photosynthetic electron transport in chloroplasts, driving electrons from reduced ferredoxin to NADP 1 . This reaction is rate limiting for photosynthesis under a wide range of illumination conditions, as revealed by analysis of plants transformed with an antisense version of the FNR gene. To investigate whether accumulation of this flavoprotein over wild-type levels could improve photosynthetic efficiency and growth, we generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(54 citation statements)
references
References 55 publications
2
51
1
Order By: Relevance
“…Previous transformation of tobacco (Nicotiana tabacum) with pea FNR did not yield a phenotypic difference (Rodriguez et al, 2007), indicating that factors other than FNR limit photosynthesis in tobacco. It was recently reported that expression of rice (Oryza sativa) FNR2 in Arabidopsis perturbed both LET and CET, while rice FNR1 disturbed N assimilation (Higuchi-Takeuchi et al, 2011).…”
Section: Differential Roles Of Membrane-bound and Soluble Fnr In Cetmentioning
confidence: 99%
“…Previous transformation of tobacco (Nicotiana tabacum) with pea FNR did not yield a phenotypic difference (Rodriguez et al, 2007), indicating that factors other than FNR limit photosynthesis in tobacco. It was recently reported that expression of rice (Oryza sativa) FNR2 in Arabidopsis perturbed both LET and CET, while rice FNR1 disturbed N assimilation (Higuchi-Takeuchi et al, 2011).…”
Section: Differential Roles Of Membrane-bound and Soluble Fnr In Cetmentioning
confidence: 99%
“…However, increases in protein levels of photosynthetic electron transport chain components, except for overexpression of cytochrome c6 (Cyt c 6 ) from the red alga Porphyra yezoensis, did not result in increase in FPSII and plant growth [ferredoxin NADP(H) oxidoreductase, Rodriguez et al, 2007;ferredoxin, Yamamoto et al, 2006]. Overexpression of Porphyra Cyt c 6 in Arabidopsis resulted in enhanced ETR through PSII and plant growth and an increase in NADPH and ATP (Chida et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in vivo have revealed that suppression of FNR expression leads to increased susceptibility to photo-oxidative damage, impaired plant growth and lowered photosynthetic activity of transgenic plants (Hajirezaei et al, 2002;Palatnik et al, 2003). On the other hand, overexpression of FNR results in slightly increased rates of electron transport from water to NADP+ and increased tolerance to oxidative stress (Rodriguez et al, 2007). Based on isoelectric focusing and SDS-PAGE the proteome of wheat has revealed four distinct leaf FNR isoforms that can be divided into two groups, FNRI and FNRII.…”
Section: Fnr Gene Familiesmentioning
confidence: 99%
“…The redox poise of the NADP(H) pool is also likely to regulate photosynthetic electron transfer activity in order to balance production and consumption of reducing equivalents, and thereby to limit production of ROS in the chloroplasts (Hald et al, 2008). Overexpression of FNR, however, did not markedly up-regulate the rate of NADP + photoreduction or CO 2 assimilation, but showed increased tolerance to photodamage (Rodriguez et al, 2007). Fig.…”
Section: Fnr Trol and Tic62 Arabidopsis Mutantsmentioning
confidence: 99%
See 1 more Smart Citation